دور الإعلام السمعي في غرس القيم الإيمانية لدى الأسرة المسلمة - رحماني ،شيماء (University of Eloued جامعة الوادي, 2024)
"ملخص البحث: تتناول ىذه الدراسة ""دور اإلعالم السمعي يف غرس القيم اإلؽلانية لألسرة ادلسلمة"" من خالل حتليل العوامل ادلختلفة ادلؤثرة يف فعالية ىذا اإلعالم. تسلط الدراسة الضوء على األعلية ادلتزايدة لإلعالم السمعي كوسيلة لنقل القيم الدينية وتعزيز الوعي اإلسالمي يف سياقات أسرية متعددة . استندت الدراسة إىل مراجعة شاملة لألدبيات ادلعنية، حيث استنتجت أن اإلعالم السمعي، مبا يف ذلك اإلذاعات التقليدية والبودكاست، ؽلثل أدوات فعالة لنشر ادلعلومات الدينية، شلا يسهم يف تعزيز الفهم الصحيح للقيم اإلسالمية. كما أبرزت النتائج الدور احليوي الذي تلعبو العوامل االجتماعية والثقافية يف استجابة األسر حملتوى الربامج السمعية، حيث تساىم ىذه العوامل يف تشكيل توجهات اجلمهور ومدى تفاعلو مع ادلواد اإلعالمية. ً إىل ضرورة تعزيز التعاون دعت الدراسة أيضا بٌن ادلؤسسات الدينية والرتبوية واإلعالمية لضمان تقدمي زلتوى موثوق وذا جودة عالية، يتماشى مع القيم اإلسالمية. كما أكدت النتائج على أعلية تعزيز ُعزز التفاعل بٌن األسر واحملتوايت السمعية، من خالل النقاشات األسرية واسرتاتيجيات تعليمية موجهة ت من الفهم العميق للقيم الدينية. أوصت الدراسة ابالستفادة من التقنيات احلديثة يف تطوير احملتوى اإلعالمي السمعي، كما ً حبثية مستقبلية تركز على أتثًن اإلعالم السمعي الرقمي وكفاءتو يف غرس القيم اإلؽلانية. ت قدمت آفاقا ُ ىذه الدراسة خطوة مهمة ضلو تطوير اسرتاتيجيات فعالة تضمن تعز ليب احتياجات الثقافة اإلسالمية وت "The Role of Audio Media in Instilling Faith Values in Muslim Families: A Descriptive Analytical Study Abstract: This study titled ""The Role of Audio Media in Instilling Faith Values in Muslim Families"" examines the various factors influencing the effectiveness of this media. It highlights the increasing importance of audio media as a means of conveying religious values and enhancing Islamic awareness in diverse family contexts. The study is based on a comprehensive review of relevant literature, concluding that audio media, including traditional radio and podcasts, serves as effective tools for disseminating religious information, thereby contributing to a better understanding of Islamic values. The findings also emphasize the vital role that social and cultural factors play in shaping families' responses to audio programs, as these factors influence audience attitudes and their engagement with media content. The study calls for enhanced collaboration between religious, educational, and media institutions to ensure the delivery of reliable and high-quality content that aligns with Islamic values. It further underscores the significance of fostering interaction between families and audio content through family discussions and targeted educational strategies to deepen the understanding of religious values. Additionally, the study recommends utilizing modern technologies to develop audio media content, offering future research avenues that focus on the impact and effectiveness of digital audio media in instilling faith values. This study serves as an important step toward developing effective strategies that ensure the promotion of Islamic culture while meeting the needs of contemporary society."
مذكرة ماستر تخصص دعوة وثقافة واسلامية
Keywords: العالم السمعي; الاسرة المسلمة; Muslim family; The audio world